2019
DOI: 10.3390/bs9060065
|View full text |Cite
|
Sign up to set email alerts
|

A Relational View of Psychological Empowerment and Sense of Community in Academic Contexts: A Preliminary Study

Abstract: Scholars need to pay attention to understand the factors that shape the interactions between individuals and social groups. Constructs like Psychological Sense of Community (PSoC) and Psychological Empowerment (PE) are powerful constructs used to evaluate the antecedents and the consequences of individual attachment to social settings. In parallel, recent advances in network analysis show that the position occupied within whole networks and ego-centric networks are relational factors that affect the subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The sense of community is directly linked to building resilient social ties (Skoultsos et al, 2020). Hence, the sense of belonging to a community is interpreted as a social bond with emotional connotations (Hamn et al, 2016), that is, the individuals of a group maintain ties and interact with other members of the same group (Ramos-Vidal, 2019). Conference attendees are usually members of various associations that organise the conferences, but they do not get involved in them in the same way, attending those conferences that are most highly rated, with a higher level of experts in the field (Oppermann and Chon, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The sense of community is directly linked to building resilient social ties (Skoultsos et al, 2020). Hence, the sense of belonging to a community is interpreted as a social bond with emotional connotations (Hamn et al, 2016), that is, the individuals of a group maintain ties and interact with other members of the same group (Ramos-Vidal, 2019). Conference attendees are usually members of various associations that organise the conferences, but they do not get involved in them in the same way, attending those conferences that are most highly rated, with a higher level of experts in the field (Oppermann and Chon, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A high level of sense of community can enhance emotional communication and a sense of autonomy among users in a community environment. By enhancing the sense of belonging of community members, community members' valuable behaviors toward society can be enhanced [78]. In addition, we also found that when users in virtual communities maintained a high level of sense of belonging and free control of the community, user interaction in virtual communities was more significant to the perceived relationship between customer citizenship behaviors through psychological empowerment.…”
Section: Discussionmentioning
confidence: 59%
“…One of the extensively applied concepts to understand the connections of individuals to social groups is a sense of community (feel of responsibility). The development of these psychological elements on oneself lies in their involvement in community activities (10). A sense of community is usually related to the pride of belonging to a place and can be influenced by the perceived livability.…”
Section: Personality-specific Belief: Sense Of Communitymentioning
confidence: 99%